The Impact of manufactured imports from developing countries in the Federal Republic of Germany - Frank Wolter (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1980)
Significant changes in the structure of production and employment are one of the salient features of West Germany's economic history. However, it was not until the mid-1970s that such changes were accompanied by sizeable friction. After 1973, the hitherto last year of full employment, the German economy has been characterized by disequilibria on the labour market and a fairly poor investment and economic growth performance as measured by prior standards. Obviously, since a couple of years the demand for adjustment in Germany, as in most other western industrialized countries, has outpaced the economy's adjustment capacity. Whether or to what extent the adjustment difficulties are due to an increase in demand for structural change or to a decrease of the economy's flexibility cannot be precisely assessed. (I) In the course of the 1970s, various shocks have added to necessary adjustment to shifts in relative prices that are considered normal in the course of economic growth. (II) At the same time, observed increases in price and wage rigidities (Soltwedel, Spinanger, 1976; Fels, Weiss, 1978; Glismann et al., 1973) seem to have weakened the allocative efficiency of the market mechanism in the 1970s as compared to the 1960s. Among the factors mentioned to exert pressure for structural change in Germany, the present paper aims at investigating the adjustment in response to an increasing division of labour with developing countries. The focus of the paper is on manufacturing in which adjustment pressure has become particularly strong. The years 1965, 1969, 1973 and 1977, i.e. periods of relatively high capacity utilization, serve as benchmarks.
Keywords: 330